2004
DOI: 10.3354/meps284227
|View full text |Cite
|
Sign up to set email alerts
|

Life history of Nippoleucon hinumensis (Crustacea: Cumacea: Leuconidae) in Seto Inland Sea of Japan. II. Non-diapausing subpopulation

Abstract: The great majority of Nippoleucon hinumensis (Gamô) in the Seto Inland Sea of Japan enters a long-term summer diapause from May to November. We identified a minor subpopulation of N. hinumensis (0.7% of the total population) that became adults in a short period without diapause. Small-sized ovigerous females (15% shorter than the ordinary-sized ovigerous females) appeared from January to early February, a month earlier than the appearance of the ordinary-sized ovigerous females that produce diapausing offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Although males became markedly less abundant than females after incubation of the first brood, all females could nevertheless incubate a second brood. The females may retain spermatozoa required for the second brood in their body for the second brood, but another possibility is proposed in Akiyama & Yamamoto (2004). In the present study, adult individuals, especially preparatory females, showed a patchy distribu-tion on the seabed.…”
Section: Reproductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Although males became markedly less abundant than females after incubation of the first brood, all females could nevertheless incubate a second brood. The females may retain spermatozoa required for the second brood in their body for the second brood, but another possibility is proposed in Akiyama & Yamamoto (2004). In the present study, adult individuals, especially preparatory females, showed a patchy distribu-tion on the seabed.…”
Section: Reproductionmentioning
confidence: 52%
“…The duration from emergence to entering the diapause was too short for larvae derived from the second brood to have grown fully and reached the 2nd juvenile instar stage. The small subpopulation of individuals derived from the second brood may not affect the total population of N. hinumensis, but there is a possibility (Akiyama & Yamamoto 2004) that they play a pivotal role in maintaining a subpopulation of individuals without a diapause during their life span (nondiapausing individuals).…”
Section: Reproductionmentioning
confidence: 99%
See 1 more Smart Citation